Vaccination status of tribal mothers and their under five children - Rahman, M; Banerjee, M; Rahman, M; Akhter, FU (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jan;15(1):55-7 The abstract of this article is available on the PubMed website